PENGARUH TAYANGAN HUMOR TERHADAP SHORT TERM MEMORY PADA MAHASISWA BARU FAKULTAS PSIKOLOGI UMGO - Lenny Syamsuddin; Frendy A. Kadir; Fitrah R. Podungge; Sri Antiwi Noho; Alya F. Faddya; Amelia M. Bidjuni; Gabriel V. Walukow (Elsia: Jurnal Psikologi Manusia, 2023)
This research examines the effect of humorous shows on the short-term memory of new students at the Faculty of Psychology, Muhammadiyah University of Gorontalo (UMGo) class of 2024. Using a two-group experimental design, subjects were asked to remember short stories after being given humorous shows (experimental group) or without humorous shows (control group). The t-test results showed that there was no significant difference between the two groups (p=0.530), which indicated that humorous displays did not significantly influence short-term memory. Environmental factors, short treatment duration, and confounding variables are thought to influence the results. Further research with better variable control and intensive treatment is recommended to obtain more valid findings.